A contribution to drinking water sources protection strategies in a portuguese river basin - Vieira, J. M. Pereira (1999)
The need and growing interest on raw water sources protection is a great concern in river basin planning and management. Problems related to drinking water sources can range from shortage of water to water quality degradation mainly due to intensive urbanisation and industrial policies as well as uncontrolled agricultural practices. The river Cavado basin, located in the north-western region of Portugal, has a very intensive use for water supply, irrigation and hydropower generation. New water supply project serving the Oporto Metropolitan Area, with one million people and a design flow of 2.7 m3/s, will introduce new challenges in the river water quality management. Since the river Cavado flow regime is artificially controlled by reservoirs, a flow discharge policy is needed. Moreover, the consideration of wastewater loads in the basin  wastewater treatment plant (WWTP) effluent discharges, untreated industrial wastewater discharges and agricultural diffuse pollution  must be considered to guarantee adequate river water quality for drinking water supply purposes. This paper illustrates the application of a decision support system (DSS) methodology in the river basin, and describes the results obtained from the simulation of the river water quantity and quality, considering various planning scenarios, in order to establish operational standards at the new water treatment plant (WTP).